2019
DOI: 10.1590/1089-6891v20e-43072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antioxidant Supplementation in Diets of Roosters During the Post-Peak Phase on Reproduction and Production Characteristics of Offspring

Abstract: This study aimed to evaluate the effects of antioxidant supplementation in diets of breeding roosters during the post-peak phase on reproduction characteristics and muscle performance of offspring in two similar breeder houses from a local company. Treatments consisted of a control diet and a diet supplemented with antioxidants (8 ppm canthaxanthin + 40 ppm lycopene + 150 ppm vitamin C). During the 66th week of age, eggs were incubated, and offspring were housed. Dietary supplementation of the blend of antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…The epigenetic marks are inheritable and capable of turning genes on or off in progeny. Despite this, there is still little understanding of transgenerational epigenetics in animals [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epigenetic marks are inheritable and capable of turning genes on or off in progeny. Despite this, there is still little understanding of transgenerational epigenetics in animals [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Roosters have an essential role in the broiler breeding system, where they constitute 50% of the genetic make-up of progeny and the flock fertility [ 25 ]. Methionine is an essential nutrient that promotes rooster semen production and improves semen quality [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In rabbits, dietary seaweed supplementation at 2% reduced sperm concentration, percentage of live sperm, and ejaculate volume (Okab et al, 2013). Due to that CX is belonging to carotenoids, which have great oxygen restoration capability, it represent a tool to reduce oxidative stress (Damaziak et al, 2018; Triques et al, 2019), and enhances the number of spermatozoa (Mahmoodpour et al, 2017). The existing results correspond with those obtained by Ferreira (2010) who stated that dietary CX supplementation to the White Plymouth Rock roosters resulted in an increase in sperm motility and concentration and a decrease in sperm morphological anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Spirulina can be used to inhibit peroxidation because of its high content of protein, essential fatty acids, vitamins, carotenoids, and antioxidants and that caused an increase in fertility and hatchability (Abouelezz, 2017; Aljumaily & Taha, 2019; El‐Bahr et al, 2020). Birds fed diets supplemented with SP and/or CX showed high percentages of fertility and hatchability due to the role of these supplementations as antioxidants (Abu Hafsa et al, 2019; Michalak & Mahrose, 2020; Triques et al, 2016, 2019). The current results are in line with those obtained by Farag et al (2015) who reported that SP increases fertility and hatchability rates in poultry species.…”
Section: Discussionmentioning
confidence: 99%
“…Niki (1987) melaporkan bahwa vitamin C memiliki kemampuan meregenerasi potensi antioksidan vitamin E dengan menyumbangkan elektron askorbat ke radikal tokoferil. Triques et al (2019) melaporkan bahwa penambahan pakan dengan sumber antioksidan (8 ppm canthaxanthin + lycopene 40 ppm + 150 ppm vitamin C) meningkatkan kinerja reproduksi ayam jantan.…”
Section: Suplementasi Antioksidanunclassified